Distribution Patterns of Beautiful Beetle Species in Suranadi Nature Park, Lombok, Indonesia - Ilhamdi, Mohammad Liwa; Idrus, Agil Al; Santoso, Didik; Raksun, Ahmad; Syazali, Muhammad (Jurnal Biologi Tropis, 2024)
Beautiful beetles are a group of insects that play an important role in maintaining ecosystem balance, ecotourism and education. Suranadi Nature Park, as one of the conservation areas in Indonesia, has great potential in maintaining the biodiversity of these insects. However, information on the dispersion pattern of beautiful beetle species in this area is still very limited so this research is important. The data collection method was carried out by survey, by capturing and directly documenting the beetles encountered during the exploration of the forest of TWA Suranadi. Data collection was carried out in June 2024 on the edge, middle of the forest and waterways. The samples obtained were brought to the Biology Education laboratory of FKIP Unram for identification. The results showed that the distribution pattern of beautiful beetles in Suranadi Nature Tourism Park has three distribution patterns, namely group distribution patterns of 21%, Uniform 72% and random distribution patterns 7%. In conclusion, the distribution pattern of beautiful insects in Suranadi Nature Park is different. The dominant uniform distribution pattern, then the group distribution pattern and the least random distribution pattern.